Pengaruh Edukasi Kesehatan Terhadap Perubahan Peran Pada Ibu Postpartum Remaja Dengan Defisit Pengetahuan: Studi Kasus - Eka Sari, Yusinta; Sumaryani, Sri; Wulandari, Noor (Pustaka Galeri Mandiri, 2025)
The postpartum period is an important period for mothers after giving birth, especially for adolescents who are in the transition period towards adulthood. Adolescent mothers tend to face physical and psychological challenges and experience limited knowledge in caring for themselves and their babies due to unpreparedness to play the role of a mother. One effective intervention to overcome this problem is health education through health promotion media. This study aims to improve the knowledge of adolescent mothers regarding postpartum care, breastfeeding, and newborn care, as well as strengthen self-confidence in carrying out the role of a mother. The method used is a descriptive study with a case study approach on one adolescent postpartum patient who experienced a knowledge deficit. Data collection techniques include interviews, physical examinations, Gordon function pattern assessments, observations, and medical record reviews. Nursing interventions are provided in accordance with the Indonesian Nursing Intervention and Outcome Standards. The results showed an increase in understanding, active participation in education, and initial skills in breastfeeding and self-care practices. In conclusion, health education through promotion media has proven effective in improving the understanding and readiness of adolescent mothers to undergo the postpartum period.